Advanced Rubber Composites - Heinrich, Gert.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Morphology–Property Relationship in Rubber-Based Nanocomposites: Some Recent Developments, by A. K. Bhowmick, M. Bhattacharya, S. Mitra, K. Dinesh Kumar, P. K. Maji, A. Choudhury, J. J. George and G. C. Basak; * Rubber–Clay Nanocomposites: Some Recent Results, by Amit Das, De-Yi Wang, Klaus Werner Stöckelhuber, René Jurk, Juliane Fritzsche, Manfred Klüppel and Gert Heinrich; * Surface Modification of Fillers and Curatives by Plasma Polymerization for Enhanced Performance of Single Rubbers and Dissimilar Rubber/Rubber Blends, by J. W. M. Noordermeer, R. N. Datta, W. K. Dierkes, R. Guo, T. Mathew, A. G. Talma, M. Tiwari and W. van Ooij; * Recent Developments on Thermoplastic Elastomers by Dynamic Vulcanization, by R. Rajesh Babu and Kinsuk Naskar; * PTFE-Based Rubber Composites for Tribological Applications, by M. S. Khan and G. Heinrich.
Morphology–Property Relationship in Rubber-Based Nanocomposites: Some Recent Developments, by A. K. Bhowmick, M. Bhattacharya, S. Mitra, K. Dinesh Kumar, P. K. Maji, A. Choudhury, J. J. George and G. C. Basak -- Rubber–Clay Nanocomposites: Some Recent Results, by Amit Das, De-Yi Wang, Klaus Werner Stöckelhuber, René Jurk, Juliane Fritzsche, Manfred Klüppel and Gert Heinrich -- Surface Modification of Fillers and Curatives by Plasma Polymerization for Enhanced Performance of Single Rubbers and Dissimilar Rubber/Rubber Blends, by J. W. M. Noordermeer, R. N. Datta, W. K. Dierkes, R. Guo, T. Mathew, A. G. Talma, M. Tiwari and W. van Ooij -- Recent Developments on Thermoplastic Elastomers by Dynamic Vulcanization, by R. Rajesh Babu and Kinsuk Naskar -- PTFE-Based Rubber Composites for Tribological Applications, by M. S. Khan and G. Heinrich.
Keywords: Polymers .; Medicinal chemistry; Pharmacy; Biochemistry; Electrochemistry; Polymer Sciences; Medicinal Chemistry; Pharmacy; Biochemistry, general; Electrochemistry